The evolution of women in labor market and the current situation: considerations on the financial sector (Research, Society and Development, 2022)
The present work deals with the evolution of women in the labor market, focusing on the current situation of women in this environment. It can be said that women's work occurred in all times and places in the world, as women have always worked, even though this was not always the exercise of “professions”, they have always had domestic labors. Through the evolution of modern times, it can be said that women have increasingly conquered their spaces, however, this does not exempt them from difficulties. Before the establishment of subordination bonds between the sexes, societies were structured through equitable practices, a situation that has changed over time. Research has shown that women have gained more space in the labor market over the years, but however much the situation has evolved, it should not be forgotten that the wage gap still exists and is a problem. Many times, the woman is judged by the possible double journey, for getting pregnant and even for hormonal factors. And, even though they have higher qualifications, when thinking about higher education, they have several other daily challenges. Thus, it was concluded that companies currently should seek to employ men and women equally as an inclusion practice, but they should also seek to verify their professional qualifications, as these will dictate what someone can do professionally, benefiting the organization.